EFFECT OF HYPNOTHERAPY IN REDUCING PHOBIA SYMPTOMS - Moh Sarifudin S. Auna (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2020)
A phobia from the perspective of psychoanalysis is a traumatic experience of the past which is repressed into the unconscious. Hypnotherapy is used to help someone easily, quickly, effectively, efficiently in reaching the subconscious mind, re-educating, reducing physiological and psychological symptoms caused by phobias and giving them more control in everyday situations. The purpose of this study was to determine the effectiveness of hypnotherapy in reducing phobia symptoms. This research is aresearch pre-experimental using one-group pre-post test design. Participants numbered 20 people. The sampling technique used sampling incidental. The questionnaire in this study used the Fear Questionnaire (FQ). The results showed a characteristic age of 22 years, the majority of phobias were found in 80% women and 20% men. Based on the paired sample t-test results obtained data indicate that thevalue Asymp. Sig. 0,000 <0.05, which means that there is a significant change in the decrease in phobia symptoms by 51.87% after hypnotherapy. This study concluded that hypnotherapy was effective in reducing phobia symptoms with 2 therapy sessions in 4 meetings.